Cold season mortality and hatching behavior of Aedes aegypti L. (Diptera: Culicidae) eggs in Buenos Aires City, Argentina - Fischer, Sylvia (2011)
In temperate regions, populations of Aedes aegypti survive the cold season in the egg stage. In the present work, we studied the cold-season mortality of Ae. aegypti eggs and their subsequent hatching pattern in Buenos Aires city. Eggs were exposed during the winter season (three months) in three neighborhoods located along a gradient of distance toward the Río de la Plata River, coincident with a gradient of activity of Ae. aegypti. Results showed mortalities lower (30.6%) than those from tropical regions during the dry season. Significant differences were detected among the egg mortalities of each site with a maximum value at the site nearest the Río de la Plata River (50%), and a minimum value at the most continental site (9%). Post-experimental hatching response of eggs differed between sites, with the highest proportion of hatched eggs during the first immersion in the site nearest to the river and the lowest proportion in the most continental site. The hatching proportion also differed between age classes, with older (early-laid) eggs hatching later than new (late-laid) ones. Our results provide the first information of Ae. aegypti egg mortality in temperate South America and support the hypothesis that differences in egg mortality are associated with abundance patterns of Ae. aegypti in Buenos Aires city.